2017
DOI: 10.1021/acs.energyfuels.7b01322
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalyzed Accelerated Post-combustion CO2 Capture and Stripping in Monoethanolamine

Abstract: The existing solvent-mediated CO2 capture process is energy-intensive as a result of the high-temperature requirement for solvent regeneration. Therefore, improvement of solvent systems for optimized and low-energy-intensive CO2 capture and desorption is of enormous interest. In this regard, we report a novel matrix composed of ZnO/Fe2O3-encapsulated mesoporous silica-tethered thermostable carbonic anhydrase (CA) (designated as CA@fn-Zn/Fe/MS). The enzyme-coupled matrix was used for efficient post-combustion C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…used for less energy-intensive desorption of CO scrubber for solvent recovery [19,20]. The multi-enzyme approach is more advantageous over the single enzyme systems.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…used for less energy-intensive desorption of CO scrubber for solvent recovery [19,20]. The multi-enzyme approach is more advantageous over the single enzyme systems.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Recently, an innovative approach for greatly reducing heat duty of amine solvent regeneration was proposed in our earlier works. , The use of acid catalysts for the CO 2 desorption process mainly decreases the sensible heat and evaporation heat by donating the proton to aid the breakdown of carbamate and lowering the desorption temperature from 120 to 140 °C to a temperature less than 100 °C. , The results demonstrated that the introduction of the solid acid catalysts into the rich amine solvent could significantly reduce the energy requirement. Various solid catalysts, such as zeolites, metal oxides, sulfated metal oxides, carbonic anhydrase, and metal modified zeolites, have been evaluated for this objective. ,,, A brief review of investigations for the catalytic rich MEA solution regeneration process over solid acid catalysts is summarized in Table S3. Note that compared with the catalyst-free run, the addition of the different solid acid catalysts with 5 M MEA lowered the energy consumption by approximately 10–34% and increased the quality of released CO 2 by approximately 10–94%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The solid acid catalysts like zeolite molecular sieve, [16][17][18] transition metal oxides, 19,20 hydroxy metal oxides, 15 sulfated metal oxides, 21,22 metal ion mediated, 23 and thermostable carbonic anhydrase 24 were usually applied for the CO 2 desorption from CO 2 -rich MEA solution.…”
Section: Introductionmentioning
confidence: 99%